PERAN WALISONGO DALAM MENTRANSFER TASAWUF - Kasman Kasman (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2018)
Sufism originally entered in the archipelago was brought by walisongo. The famous scholar in spreading Islam in the area of ​​Java Island is "walisongo". In the struggle in developing Islam, many wisdom that can be taken and emulated. The strategy they use can be accepted by many people, from the bottom to the upper classes of the nobles and kings. This is because the walisongo wearing tasawuf knowledge in da'wah, so much in demand by various circles. Walisongo is nine people who have been able to reach the level of guardian, a high degree of degree that is able to escort babanga sanga (guarding the nine holes in human beings), so it has a ranking guardian who spread Islam in Java. The teachings of Sufism that are taught include tasawuf akhlaqi and tasawuf falsafi. How to teach through 1) Da'wah with Education, Institution and Science of Wisdom; 2) Using wisdom and acculturation of Islamic teachings with local culture; 3) Acculturating the arts with the teachings of Sufism.